Neuroprotective Effects and Hepatorenal Toxicity of Angong Niuhuang Wan Against Ischemia–Reperfusion Brain Injury in Rats - Tsoi, Bun; Chen, Xingmiao; Gao, Chong; Wang, Songlin; Yuen, Sau Chu; Yang, Depo; Shen, Jiangang (Frontiers in Pharmacology, 2019)
Angong Niuhuang wan (AGNHW) is a classic prescription in Traditional Chinese Medicine (TCM) used for stroke treatment, but its efficacies remain to be confirmed. With its arsenic- and mercury-containing materials, the application of AGNHW raises great safety concerns. Herein, we aim to explore the neuropharmacological effects against cerebral ischemia-reperfusion injury and evaluate the toxicological effects of AGNHW for better use. Male SD rats were subjected to 2 hours of middle cerebral artery occlusion (MCAO) and following 22 hours of reperfusion. AGNHW (257 mg/kg, 1× AGNHW) were orally administrated for pharmacological effects and 257, 514 and 1028 mg/kg (equivalent to 1×, 2×, 4× AGNHW) were used for the toxicological study. The results revealed that AGNHW treatment reduced the infarct size and protected the blood-brain barrier (BBB) integrity in the MCAO rat ischemic stroke model. AGNHW treatment up-regulated bcl-2 expression and down-regulated the expressions of Bax, p47phox, inducible nitric oxide synthase (iNOS) and 3-nitrotyrosine (3-NT), and inhibited the expressions and activities of matrix metalloproteinase-2 (MMP-2), MMP-9 and reserved tight junction protein zonula occludens-1 (ZO-1) and claudin-5 in the ischemic brains. These results indicated the neuroprotective mechanisms of AGNHW could be associated with its antioxidant properties by inhibiting oxidative/nitrative stress-mediated MMPs activation and protecting tight junction proteins in the ischemic brains. Administration of 1×AGNHW for 7 days would not induce the accumulation of mercury in blood, liver, and kidney at day 14. Administration of 2×AGNHW and 4×AGNHW for 7 days increased the level of mercury in the kidney. For arsenic level, administration of 1×AGNHW for 7 days would increase the level of arsenic in the liver and blood without increase of arsenic in the kidney at day 14. Administration of 2×AGNHW and 4×AGNHW for 7 days would further increase the level of arsenic in the liver and blood. There is no influence on body weight, organ index, histological structures, and renal and liver functions. These results suggest that short-term treatment of AGNHW within one week should be safe and has neuroprotective effects against cerebral ischemia-reperfusion injury.